Searching Capacity of Habrobracon hebetor Say (Hymenopetra :Braconidae)for Its Host Larvae in Simulated Date Store - Maysoon Ali Shawkit; Baseem Shebab Hamad; Nabeel Abdel –Masseh Khder; Asad Alwan Hamed; Ayad Ahmed AL-Tweel (Journal of Madenat Alelem University College, 2014)
Host – finding ability by the parasite, Habrobracon hebetor Say was evaluated under waerhouse condition, the warehouse measurement were 23×21×3.30m, in which fourth and last instar larvae of Ephestia cautella were distributed inside glass containers at different distances and heights from the release point of the adult parasite of 24 hrs old. The mean number of paralyzed larvae of the host and then the number of parasitoid pupae developed from these larvae was calculated. Results showed the ability of the parasite to reach farest locations from the releasing point such as: 28.6 m with 1 m height and 24 m with 3 m height. The r2value for 1 meter height was 0.946 for mean number of larval host while the value r2 was 0.926 for mean number of pupal parasitoid developed on the host. Furthermore, the r2 value for 3 meter height was 0.761 and 0.750 for the mean number of larval host parlayzed and the mean number of parasitoid pupae developed, respectively.